The Integration Of Christian Values In The Implementation Of An Independent Curriculum In Christian Schools In Developing Student Character In The Era Of Digital Technology - Yasozatulo Larosa (Green Publisher Indonesia, 2024)
The digital era brings significant changes in various aspects of life, including education. Christian schools are faced with the challenge of integrating Christian values in the implementation of the Merdeka Curriculum amid the onslaught of digital technology. This study aims to analyze the integration of Christian values in the implementation of the Merdeka Curriculum in Christian schools in developing student character in the era of digital technology. This research uses qualitative research methods. The data collection technique in this study is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that Christian values that can be taught to children at school through the Merdeka Curriculum include love, patience, tolerance, empathy and sympathy, honesty, humility, loyalty, and responsibility. The implementation of these values in Christian schools through the Merdeka Curriculum can produce graduates with strong character and ready to face challenges in the era of digital technology. These Christian values help students build a strong and firm faith, so that they are able to face the various temptations and challenges presented by digital technology.